Long-term administration of single-agent carboplatin (AUC 4) for advanced testicular seminoma safely achieved complete response in an 80-year-old man with chronic heart failure: A case report - Fukuhara, Hiroki; Yagi, Mayu; Ando, Kaoru; Tomita, Yoshihiko (Canadian Urological Association Journal, 2014)
Carboplatin is often used instead of cisplatin as an alternative treatment for advanced testicular cancer. However, the safety, optimal dose, and optimal duration of this agent are unclear in patients with cardiac complications. We report the safety and effectiveness of long-term single-agent carboplatin for the treatment of testicular cancer in a patient with chronic heart failure (CHF). An 80-year-old man was referred to our institution for evaluation of painless swelling of the left scrotum. Computed tomography revealed lung metastases. Left radical inguinal orchiectomy was performed, and pathologic examination revealed a pure seminoma. Because he had CHF, there was high possibility of onset of acute heart failure secondary to fluid administration. Thus, single-agent carboplatin (AUC 4) was selected for therapy. A complete response was achieved after 8 of 13 cycles, and no serious adverse events occurred, including cardiac problems. Neither recurrence nor metastasis was detected during the 6-month follow-up. Low-dose, long-term carboplatin is likely effective for patients who are unfit for cisplatin administration because of comorbidities, especially CHF.